TIME IN THE VIEW OF ISLAMIC EDUCATION (CRITICAL STUDY OF SURAT AL-ASHR) - Sugianto, Relly; Hidayat, Wahyu; Wasehudin, Wasehudin (Almarhalah: Jurnal Pendidikan Islam, 2023)
Time is one of the dimensions of human life. By seeing how important the value of time is and how great the blessings of Allah SWT are contained in it. The Qur'an has given great attention to time. Al-Qur'an surah al-Asr emphasizes and pays special attention to the value and essence of time as a warning. Allah SWT . The type of research used in this research is library research, namely research that only uses library collection materials without any field research. The results of the research from the letter Al-Asr: First, Al-Asr is a letter that contains the oath of Allah Ta'ala, that there is certainty that humans in totality will suffer losses for what they do. Second, the third verse contains instructions from Allah Ta'ala to avoid losses during his lifetime by: believing in Allah and doing good deeds, instructing each other to hold on to the truth, practicing obedience to Allah and being patient in it.